(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
In this article, the leader of the Turkestan national independence movement, the founder of the Uzbek national press and the national school of the new method at the beginning of the 20th century, the writer and poet Munavvar Кori Abdurashidkhanov, the state of education in Turkestan at the beginning of the 20th century, the problems in this field and their solutions. suggestions, recommendations, ideas about.